Glacier mass-balance and length variation observed in China during the periods 1959–2015 and 1930–2014. (1st October 2017) - Che, Yanjun; Zhang, Mingjun; Li, Zhongqin; Li, Huilin; Wang, Shengjie; Sun, Meiping; Zha, Shuping
Abstract: The importance of glaciers for providing runoff is reflected in the extensive glacier measurement record for China. In this paper, we summarized the mass-balance and front-variation data of glaciers in China that have long-term records. Mass balance has been measured for 22 glaciers; length (or front-position) records exist for 96 glaciers. We found that the mean rate of glacial mass balance decreased by −0.015 m w.e. (water equivalent) per year during the period 1959–2015, which was lower than that for glaciers globally (−0.013 m w.e. per year). It was indicated that the rate of glacial melting (mass loss) increased in China, which was higher than that in glaciers worldwide. However, glacial frontal positions varied among mountains in time and space. Glaciers in the Karakoram Mountains mean advanced 379 m during the 1968–2000 period, while glaciers in the Pamir Mountains remained relatively stable from the 1960s through the 2000s, i.e., retreated 28 m. Glaciers in Hengduan Mountains retreated farthest (1250 m maximum) from 1930 to 2005.